The ambiguities of money-making: Indie video game developers and the norm of creative integrity. Issue 3 (24th October 2019) - Styhre, Alexander; Remneland-Wikhamn, Björn
Abstract : Purpose: Indie developers are part of the creative fringe of the video game industry, fashioning an identity for themselves as a community committed to the development of video games as a cultural expression and art form. In playing this role, money-making is ambiguous inasmuch as economic return is honorable if such interests remain unarticulated and execute minimal influence on the development work process, while the possibility of producing a successful commercial video game is simultaneously one of the primary motivations for new industry entrants. The paper aims to discuss this issue. Design/methodology/approach: The paper reports on the empirical material drawn from a study of indie video game developers in Sweden, a leading country for video game development. Findings: To reconcile tensions between video game development in terms of being both cultural/and artistic production and business activity, easily compromising the perceived authenticity of the subject in the eyes of audiences (e.g. hardcore gamers), indie developers distinguish between monetary motives ex ante and compensation ex post the release of the game. Indie developers thus emphasize the metonymic function of money as this not only indicates economic value and currency but also denotes a number of business practices that indie developers have otherwise avoided in their career planning as they believe these practices would restrain their creativity and skills. Originality/value: The study contributes to the scholarship on video game development, the literature on creative industries, and the economic sociology literature examining the social meaning of money and how social norms and values are manifested in professional ideologies and practices.